Melatonin enhances anti-tumor immunity by targeting macrophages PD-L1 via exosomes derived from gastric cancer cells. (1st June 2023) - Wang, Kaifang; Cai, Rong; Fei, Shuting; Chen, Xuzheng; Feng, Sisi; Zhang, Lulu; Liu, Hui; Zhang, Zhiguang; Song, Jun; Zhou, Ruixiang
Abstract: Melatonin (MLT) is a hormone with potential anti-tumor properties, but the molecular mechanisms remain unclear. The present study aimed to explore the effect of MLT on exosomes derived from gastric cancer cells, with the goal of gaining insight into its anti-tumor activity. Results from in vitro experiments showed that MLT was able to enhance the anti-tumor activity of macrophages that had been suppressed by exosomes from gastric cancer cells. This effect was achieved through regulation of the levels of PD-L1 in macrophages via modulation of the associated microRNAs in the cancer-derived exosomes. Furthermore, MLT treatment increased the secretion of TNF-α and CXCL10 by the macrophages. Besides, MLT treatment of gastric cancer cells led to the production of exosomes that promoted the recruitment of CD8 + T cells to the tumor site, resulting in inhibition of tumor growth. Collectively, these results provide evidence for the modulation of the tumor immune microenvironment by MLT through regulation of exosomes derived from gastric cancer cells, suggesting a potential role for MLT in novel anti-tumor immunotherapies. Graphical abstract: MLT enhances the antitumor immune function of macrophages through the modulation of exosomes derived from gastric cancer cells, thereby mediating its antitumor activity. Image 1 Highlights: Gastric cancer cell-derived exosomes can impair macrophage anti-tumor immune. Melatonin enhances macrophage anti-tumor immunity via gastric cancer exosomes. Melatonin regulates PD-L1 protein and miRNAs in gastric cancer exosomes. Melatonin decreases PD-L1 level in macrophages via gastric cancer derived exosomes.